Revitalizing Local Cultural Values through Indonesian Language Learning in Elementary Schools - Damari, Niska; kasmawati, kasmawati (International Journal of Management and Education in Human Development, 2025)
Revitalizing local cultural values is crucial for maintaining national identity amidst increasingly massive globalization. Elementary schools, as the foundation of basic education, play a strategic role in internalizing local cultural values in students from an early age. Indonesian language learning is an effective vehicle for instilling these values because it encompasses a variety of language skills rich in local content, such as reading folklore texts, writing pantun (rhymes), discussing customs, and presenting cultural observations. This literature review aims to examine in depth how Indonesian language learning in elementary schools can be utilized as a medium for revitalizing local culture. This research was conducted by reviewing various previous research results, scientific articles, and educational policy documents. The study results indicate that integrating local cultural values into Indonesian language learning not only enriches students' linguistic competence but also strengthens their character, identity, and love for regional cultural heritage. The strategies used include a culture-based thematic approach, the use of locally based texts, and creative activities based on regional stories. This study recommends the need for teacher training, the development of locally culture-based teaching materials, and educational policy support that supports cultural preservation through learning. Thus, Indonesian language learning can become a meaningful space for shaping a younger generation that is not uprooted from its cultural roots.